Recipient of UMPSA-German Dual Degree Academic Excellence Prize best graduate in Hochschule Reutlingen - Nur Hartini, Mohd Hatta (UMPSA, 2023)
GAMBANG, 21 October 2023 – The dual degree programme that started in 2010 has seen 293 students successfully graduate and are now all over the globe with different expertise including Joel Marianus Mukui, 27 who successfully obtained the UMPSA-German Dual Degree Academic Excellence Prize.